Association of circulating branched-chain amino acids with risk of cardiovascular disease: A systematic review and meta-analysis. (June 2022) - Wang, Yaqin; Huang, Keyong; Liu, Fangchao; Lu, Xiangfeng; Huang, Jianfeng; Gu, Dongfeng
Abstract: Background and aims: We conducted a systematic review with meta-analysis of non-prospective and prospective clinical studies to assess the effects of circulating branched-chain amino acids (BCAA), including Isoleucine, Valine and Leucine, on cardiovascular disease (CVD) risk. Methods: PubMed, Embase, Cochrane and CNKI databases were searched for publications reporting the relationship between BCAAs and CVD. Relative risk (RR) and odd ratios (OR) were extracted and pooled. Subgroup analysis and meta-regression were performed to identify potential sources of heterogeneity, sensitivity analysis was conducted to assess the robustness of pooled estimates. Results: 11 non-prospective studies involving 2806 participants and 10 prospective studies involving 43, 895 participants reported correlations between BCAAs and CVD risk. Levels of circulating BCAAs changed in individuals with CVD compared with those in the control group. Nine prospective studies were meta-analyzed and highlighted a 10% higher risk of CVD per study-specific SD difference for Isoleucine (pooled relative risk 1.10 [1.03–1.18]; I 2 = 63.5%). Valine and Leucine do not appear to be associated with CVD incidence. Subgroup analysis based on age suggested that among adults ≤60 years, there is a 15%, 13%, and 9% higher risk of developing CVD per study-specific SD difference for Isoleucine (RR 1.15 [1.11–1.19]; I 2 = 0.0%), Valine (RR 1.13 [1.09–1.17]; I 2 = 0.0%), and Leucine (RR 1.09 [1.03–1.16]; I 2 = 40.5%), respectively. No such associations were observed for adults older than 60 years. Conclusions: Evidence suggests that elevated concentrations of circulating Isoleucine were associated with increased risks of CVD, independent of traditional risk factors. Graphical abstract: Image 1 Highlights: Higher circulating level of Isoleucine is associated with an increased risk of CVD, whereas Valine and Leucine are not. Studies involving younger people (≤ 60 years old) exhibit significant associations between higher Valine, Leucine and Isoleucine levels with increased risk of CVD, while elder people (>60 years old) not. Alterations in circulating BCAAs may be therapeutic targets for CVD risk, especially for people younger than 60 years.